Implementing the Right to Information as a Key Element of Freedom of Expression in the BRICS Countries - K. Ivanova; M. Myltykbaev (BRICS Law Journal, 2022)
The category of rights and freedoms, including the right to access information and the right to self-expression, is not immutable. Rights and freedoms are a byproduct of the historical development of society and represent a socio-cultural phenomenon that reflects the historical identity of peoples and countries throughout the world. As a result, each legal system has its own legal concept of rights and freedoms, without which the crisis-free development of a particular state is impossible. This is because the degree to which citizens’ rights to self-expression and information are realized has a direct impact on the overall quality of a democratic system. This article analyzes the sectoral normative legal acts of the BRICS countries that regulate the right to information. Based on the data obtained, a comparison was made between restrictions and prohibitions regarding the exercise of the right to information. Furthermore, the article describes and analyzes the main approaches to assessing and determining the index of democracy in the world. Based on the comparison of the democracy index, the global ranking of the right to information and the global ranking of the civilian population, a formula for calculating democracy was derived. The degree of democracy in the BRICS countries was then calculated using the formula obtained, and a regional ranking of democracy within the BRICS countries was compiled. The authors believe that providing citizens with the opportunity to fully exercise their right to information, which would be impossible without the balanced participation of the state, results in the creation of an objective information environment, which in turn provides citizens with the opportunity to justly exercise their right to self-expression. In this regard, it is self-evident that democracy is closely connected with the full realization of the right to information. Today it plays akey role in citizens’ exercise of their right to self-expression.